The Impact of Polyphenols on Nutrition and Health - Eda Adal; Tuğba Aktar (Turkish Journal of Agriculture: Food Science and Technology)
Polyphenols are plant-sourced compounds that exhibit important dietary features on human health. They have been defined and used either as a food source or as a raw material in the food industry to enhance functional properties and nutritional quality. They have significant positive bioactivities as; antioxidant, anti-inflammatory, anti-carcinogenic, cardiovascular health protection, immune supporter, and also benefits on digestion and brain functioning. The effects and bioactivity ranges were studied in the literature which has been discussed in the review to emphasize the importance of these natural compounds to provide insight into health and well-being.